Challenges and opportunities in vascularized composite allotransplantation of joints: a systematic literature review - Zhang, Lei; Hoyos, Isabel Arenas; Zubler, Cédric; Rieben, Robert; Constantinescu, Mihai; Olariu, Radu (Frontiers in Immunology, 2023)
Background Joint allotransplantation (JA) within the field of vascularized composite allotransplantation (VCA) holds great potential for functional and non-prosthetic reconstruction of severely damaged joints. However, clinical use of JA remains limited due to the immune rejection associated with all forms of allotransplantation. In this study, we aim to provide a comprehensive overview of the current state of JA through a systematic review of clinical, animal, and immunological studies on this topic. Methods We conducted a systematic literature review in accordance with the PRISMA guidelines to identify relevant articles in PubMed, Cochrane Library, and Web of Science databases. The results were analyzed, and potential future prospects were discussed in detail. Results Our review included 14 articles describing relevant developments in JA. Currently, most JA-related research is being performed in small animal models, demonstrating graft survival and functional restoration with short-term immunosuppression. In human patients, only six knee allotransplantations have been performed to date, with all grafts ultimately failing and a maximum graft survival of 56 months. Conclusion Research on joint allotransplantation has been limited over the last 20 years due to the rarity of clinical applications, the complex nature of surgical procedures, and uncertain outcomes stemming from immune rejection. However, the key to overcoming these challenges lies in extending graft survival and minimizing immunosuppressive side effects. With the emergence of new immunosuppressive strategies, the feasibility and clinical potential of vascularized joint allotransplantation warrants further investigation.